Vulnerable voices on fire preparedness: Policy implications for emergency and community services collaboration. Issue 4 (24th November 2017) - Ingham, Valerie; Redshaw, Sarah
Abstract: An investigation of household preparedness and community connections was undertaken in the NSW Blue Mountains. The research employed a qualitative approach. Upon receiving ethical approval, interviews and focus groups with a total of 31 vulnerable residents were recorded and transcribed. Data analysis included the manual coding of individual transcripts and key word queries entered into NVivo 10. Fire planning for community resilience within Australia focusses on property preparation and an emergency warning system designed to assist the evacuation decisions of residents. In this article, we report on vulnerable residents and their preparedness for the October 2013 bushfires. Our findings demonstrate that the vulnerable people interviewed did not consider property preservation as a priority, and their knowledge and engagement with the warning system and evacuation procedures was limited. Of practical value, the research found local community services and emergency planning committees should collaboratively plan for vulnerable community members who are unable to take a very active role in preparing themselves or their dependents to face a bushfire or similar disaster. In addition, preparedness and warning communications should be devised and targeted to more clearly assist vulnerable people during the lead up to, and in the midst of, a disaster.